Robot-assisted Management of Complex Ureteral Stenosis in Kidney Transplant Patients: Multicenter Case Series and Description of Surgical Techniques - Joris Vangeneugden; Federico Lavagno; Camille Berquin; Liesbeth Desender; Steven Van Laecke; Marco Oderda; Marco Allasia; Alberto Breda; Charles Van Praet; Karel Decaestecker; Paolo Gontero (European Urology Open Science, 2025)
Background and objective: Ureteral stenosis following renal transplantation can occur in up to 10% of patients. Initial management, after kidney drainage, may include endoscopic balloon dilation ± laser incision. In case of recurrence after a primary endourological approach, strictures >1–3 cm, or complex anatomy in transplant patients, ureteral reconstruction should be performed. A robotic approach may reduce morbidity in this fragile population. We describe our case series of robot-assisted surgical treatments for ureteral stenosis in kidney transplant patients. Methods and surgical procedure: We included 29 renal transplant patients who suffered from ureteral stenosis in whom ureteral reconstruction was performed at three referral centers from November 2019 to March 2024. Different approaches were used: ureteroneocystostomy (with or without an antireflux tunnel or a Boari flap), ureteroureterostomy, and pyeloureterostomy using the native ureter (ipsilateral or contralateral). Key findings and limitations: All cases were performed using the Da Vinci Xi robotic system and completed successfully without intraoperative complications. The median pre- and postoperative (3 mo) glomerular filtration rates were 45 (interquartile range [IQR] 31–60) and 46 (IQR 31–58) ml/min, respectively. The median hospital stay was 4 (IQR 3–6) d. Postoperative complications were limited (21% Clavien-Dindo ≤2 and 10% Clavien-Dindo ≥3). Of 29 patients, 28 (97%) were free from nephrostomy or JJ stent at a median follow-up of 18 (IQR 13–34) mo. Our retrospective findings advocate confirmation through prospective data. Conclusions: We demonstrate the safety and feasibility of robot-assisted ureteral reconstruction in kidney transplant patients with ureteral stenosis, allowing high-quality realignment of the urinary tract, quick recovery with a low complication rate, and good preservation of renal function in this fragile population. Patient summary: We demonstrate several robot-assisted ureteral reconstruction options for kidney transplant patients suffering from ureteral stenosis. We found these techniques to be safe and effective, with low complication rates and good preservation of the renal function.